2013
DOI: 10.1039/c3md00077j
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and antiproliferative activity of some 3-(pyrid-2-yl)-pyrazolines

Abstract: The synthesis and antiproliferative activity of eleven 3-(pyrid-2-yl)-pyrazolines in two cancer cell lines are reported. X-ray crystallography was obtained of the lead compound 8i which was screened in the NCI 60 human tumour cell line and displayed sub-micromolar activity. Cell cycle analysis, in vitro tubulin assay and confocal microscopy are also reported and suggest that the lead compound disrupts microtubule formation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
18
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 37 publications
2
18
0
Order By: Relevance
“…Continuing our interest in compounds that interact with tubulin, 1,2 we wished to investigate novel analogues of indanocine 1 (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
“…Continuing our interest in compounds that interact with tubulin, 1,2 we wished to investigate novel analogues of indanocine 1 (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
“…3,29,30 A synthetic method which employs appropriate chalcones and arylhydrazines has been considered to be the most widely accepted method for accessing pyrazolines, but this method falls behind due to a greater number of synthetic steps involved. [31][32][33][34] Recently Wang et al disclosed a methodology proceeding via a three component [3 + 2] cycloaddition using 20 mol% Cu(OTf) 2 at elevated temperature. 35 The development of synthetic methodology to prepare active pharmaceutical ingredients (APIs) would preferably involve (i) high regioselectivity, (ii) diversity in substrates, (iii) the least number of synthetic steps involved and (iv) attaining target compounds, free of metal traces.…”
mentioning
confidence: 99%
“…Some of these synthetic compounds exhibited significant cytotoxic activity. Alexander Ciupa et al 61 synthesized some 3-(pyrid-2-yl)-pyrazolines (4i) and reported the antiproliferative activity in two cancer cell lines.…”
Section: R Fioravanti Et Almentioning
confidence: 99%